FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN EPICONDYLITIS MEDIAL (GOLFER ELBOW) PADA PEKERJA MEUBEL PEMBUAT SPRINGBED - PRADANA , TEDY DIAN; ROSSA, IDJERIAH; DERI (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2015)
Golfer elbow or medial epicondylitis is irritation of the tendon that causes the tendon tears; the pronator teres muscle and flexor carpi radialis muscle. These are induced by the repetitive movements, hand arm vibration and aggravated by the attitude of a static work. Also, lifting up the workload continuously and holding vibratory a working tool trigger this irritation. The purpose of this study to determine factors associated with the incidence of medial epicondylitis (golfer's elbow) on workers springbad Bigland furniture maker PT. Dayak Lestari Ekaniaga. An observational method and a cross sectional approach were carried out in this study. The samples were 45 Bigland mattress makers. Bivariate analysis found that the Repetitive Motion P Value = 0.041 and hand arm vibration (pvalue = 0.017), the working position (P = 0.001), the load/weight of the tool (P = 0.003) and a grip (P = 0.001) associated with the incidence of medial epicondylitis (golfer's elbow). The conclusion of this study, is significant relationship between Repetitive Motion, Hand Arm Vibration, the working position (P = 0.001), the load/weight of the tool (P = 0.003) and a grip (P = 0.001) Against Genesis medial epicondylitis (Golfer Elbow) In Worker Furniture Makers Springbad Bigland Pt. Dayak Lestari Ekaniaga